Combined effects of sivelestat and resveratrol on severe acute pancreatitis-associated lung injury in rats. (3rd July 2014) - Wang, Houhong; Wang, Shuai; Tang, Amao; Gong, Huihui; Ma, Panpan; Chen, Li
ABSTRACT Despite extensive research and clinical efforts made in the management of acute pancreatitis during the past few decades, to date no effective cure is available and the mortality from severe acute pancreatitis remains high. Given that lung is the primary cause of early death in acute pancreatitis patients, novel therapeutic approaches aiming to prevent lung injury have become a subject of intensive investigation. In a previous study, we demonstrated that sivelestat, a specific inhibitor of neutrophil elastase, is effective in protecting against lung failure in rats with taurocholate-induced acute pancreatitis. As part of the analyses extended from that study, the present study aimed to evaluate the role of sivelestat and/or resveratrol in the protection against acute pancreatitis-associated lung injury. The extended analyses demonstrated the following: (1) sodium taurocholate induced apparent lung injury and dysfunction manifested by histological anomalies, including vacuolization and apoptosis of the cells in the lung, as well as biochemical aberrations in the blood (an increase in amylase concentration and a decrease in partial arterial oxygen pressure) and increases in activities of reactive oxygen species, interleukin 6, myeloperoxidase, neutrophil elastase, lung edema, bronchotracho alveolar lavage protein concentration, and bronchotracho alveolar lavage cell infiltration in the lung; and (2) in lung tissues, either sivelestat or resveratrol treatment effectively attenuated the taurocholate-induced abnormalities in all parameters analyzed except for serum amylase concentration. In addition, combined treatment with both sivelestat and resveratrol demonstrated additive protective effects on pancreatitis-associated lung injury compared with single treatment.